HUBUNGAN KARAKTERISTIK FARMAKOKINETIKA DENGAN RESPON TERAPI PADA KASUS KEGAWAT-DARURATAN PASIEN ANAK - Jamilah Jamilah; Anita Purnamayanti (CALYPTRA, 2018)
This study was aimed to find out the correlation between the characteristics of intravenous aminophylline pharmacokinetics with therapeutic response in pediatric patients with severe asthma attack and / stop breathing threat. The research design is retrospectively based on medical record at IGD RSU Haji Surabaya. Of the 36 patients receiving intravenous aminophylline from January 2016-June 2017 we obtained an estimate of pharmacokinetic parameters using population data assumption and PKPD data analysis with monolix® program obtained Vd = 0.286 liter / kg, K = 0.00564 / h, K12 = 2.41 / h , K21 = 0.0697 / h, Emax = 4.7 mg / L, and EC50 = 1.66mg / L. It was concluded that there was a relationship (p = 0,000) between the pharmacokinetics characteristics of aminophylline of intravenous infusion with therapeutic response in pediatric with severe asthma attack.